2020
DOI: 10.1007/s10815-020-01799-2
|View full text |Cite
|
Sign up to set email alerts
|

Infertility influencers: an analysis of information and influence in the fertility webspace

Abstract: Purpose To examine fertility-related social media accounts and influencers on two social media platforms. Methods The search function of Twitter (TW) and Instagram (IG) was used to generate a list of accounts with the terms: fertility, infertility, ttc, egg freezing, ivf, endometriosis, and reproductive. Accounts not in English, in private, with no posts in > 1 year, or with content unrelated to search terms were excluded. Accounts were assessed for author type; REI board certification (REI-BC); influencer (IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 8 publications
1
28
0
5
Order By: Relevance
“…In the urology community, an analysis of commercial and Medicare claims data found that fewer than 1% of urologists were using video visits in 2019 ( 2 ). In the female infertility world, before the pandemic, patients were increasingly using social media and fertility-tracking applications to obtain and engage with reproductive health information, but the use of telemedicine in patient care was far from routine ( 3 ). The rapid acceleration in the adoption of telemedicine was the consequence of public health constraints of routine in-person medical care imposed by public health officials and the removal of significant regulatory barriers by state and national governments ( 4 ).…”
mentioning
confidence: 99%
“…In the urology community, an analysis of commercial and Medicare claims data found that fewer than 1% of urologists were using video visits in 2019 ( 2 ). In the female infertility world, before the pandemic, patients were increasingly using social media and fertility-tracking applications to obtain and engage with reproductive health information, but the use of telemedicine in patient care was far from routine ( 3 ). The rapid acceleration in the adoption of telemedicine was the consequence of public health constraints of routine in-person medical care imposed by public health officials and the removal of significant regulatory barriers by state and national governments ( 4 ).…”
mentioning
confidence: 99%
“…Physicians’ communication, while preserving trustworthiness and scholarly rigor, should be accessible to the lay public, aiming at improving their health literacy, promoting healthy lifestyles, and increasing and enhancing the awareness of preventative strategies. To this end, advocacy and the celebrity effect could be exploited [ 58 , 62 ].…”
Section: Gynecology and Infodemiologymentioning
confidence: 99%
“…One significant change has been an increased use of telehealth services. Certainly, even before the current health crisis, patients were increasingly using social media and fertility tracking applications on their electronic devices to obtain and engage with reproductive health information ( 41 ). Although these technological advances may offer some benefits, it is critical to ensure the safe delivery of the highest quality care and the dissemination of accurate information.…”
Section: Con: “Online” and “At Home” Health Care Impedes Access To Opmentioning
confidence: 99%